Kesihatan dan kematian bayi di Kedah - Usman Haji Yaakob ([Minden], Pulau Pinang : Penerbit Universiti Sains Malaysia, 2008)
Demography of infant mortality, health, and hygiene in Kedah, Malaysia
Revision of the author's thesis (doctoral)--Universiti Sains Malaysia, 1995
Includes bibliographical references (p. 219-256) and index
Keywords: Infants -- Mortality -- Malaysia -- Kedah; Infants -- Health and hygiene -- Malaysia -- Kedah